Modified atmospheric packaging of cured vanilla - BIJU ABRAHAM CIBIN RAJ TANUJA P; Dr. K. P Sudheer (Guide) (Tavanur 2006 Kelappaji College of Agricultural Engineering and Technology)
Modified atmospheric packaging of cured vanilla
Modified atmospheric packaging of cured vanilla